Using intervention mapping to develop an implementation strategy to improve timely uptake of streamlined birth-dose vaccines in the Democratic Republic of the Congo. - Alix Boisson-Walsh; Bruce Fried; Christopher M Shea; Patrick Ngimbi; Nana Mbonze; Martine Tabala; Melchior Mwandagalirwa Kashamuka; Pélagie Babakazo; Marcel Yotebieng; Peyton Thompson (Public Library of Science (PLoS), 2024)
Despite the policy recommendation and effectiveness of administering the hepatitis B birth-dose vaccine (HepB-BD) to newborns to prevent mother-to-child hepatitis B transmission, timely uptake remains an issue. Countries adopting the HepB-BD to their national immunization schedule report programmatic challenges to administering the vaccine within the recommended 24-hour window after delivery. Further, while the World Health Organization recommends streamlining three birth-dose vaccines (HepB-BD, BCG, and OPV0), scarce Sub-Saharan(SSA)-based literature reports on a streamlined and timely approach to birth-dose vaccines. As more SSA countries adopt the new birth-dose vaccine to their immunization schedules, a systematically developed implementation strategy-Vaccination of Newborns-Innovative Strategies to Hasten Birth-Dose vaccines' delivery (VANISH-BD)-will facilitate the adoption and implementation of timely birth-dose vaccine uptake. In this paper, we describe the development of the implementation strategy using intervention mapping, an evidence-based and theory-driven approach. We report on the development of our intervention, beginning with the needs assessment based in Kinshasa Province, Democratic Republic of the Congo (DRC), informing step 1 of intervention mapping. The intervention is contextually relevant, locally produced, sustainable, and designed to improve timely birth-dose vaccine uptake in the DRC. We intend to inform future implementers about improving timely and streamlined birth-dose vaccine uptake and for VANISH-BD to be adapted for similar contexts.